Changes in the Concentration of Ions in Saliva and Dental Plaque after Application of CPP-ACP with and without Fluoride among 6-9 Year Old Children - Poureslami H; Hoseinifar Ra; Khazaeli P; Hoseinifar Re; Sharifi H; Poureslami P (Shiraz University of Medical Sciences, 2017)
Statement of Problem: The casein phospho peptide-amorphous calcium phosphate with or without fluoride (CPP-ACPF and CPP-ACP respectively) are of considerably new materials which are highly recommended for prevention of dental caries. However, there is a shortage in literature on how they affect the ion concentration of saliva or dental plaque. Objectives: The aim of this study was to evaluate the concentration of calcium, phosphate and fluoride in the plaque and saliva of children with Early Childhood Caries (ECC) after applying the CPP-ACP paste in comparison with the use of CPP- ACPF paste. Materials and Methods: One ml of un-stimulated saliva of 25 preschool children was collected and then 1 mg of the plaque sample was collected from the buccal surfaces of the two first primary molars on the upper jaw. CPP-ACP as well as CPP- ACPF pastes were applied on the tooth surfaces in two separate steps. In steps, plaque and saliva sampling was performed after 60 minutes. The amount of calcium ions was measured by Atomic Absorption Device and the amount of phosphate and fluoride ions was measured by Ion Chromatography instrument. Data were analyzed using Repeated Measurements ANOVA at a p < 0.05 level of significance. Results: Application of both CPP-ACPF and CPP-ACP significantly increased the concentration of calcium, phosphate, and fluoride in both saliva and dental plaque. Moreover, significantly higher salivary fluoride concentration was seen after application of CPP-ACPF compared to CPP-ACP. No other significant difference was observed between these two materials. Conclusions: CPP-ACPF can be more useful than CPP-ACP in protecting the primary teeth against caries process, especially when there is poor hygiene.